Prototipe Sistem Manajemen Tangki Pintar Berbasis Internet of Things (IoT) - hidayat, Ircham; Marlina, Marlina; Nurani, Nurani (Journal of System and Computer Engineering, 2024)
The purpose of the study was to design a prototype of a smart tank management system that aims to help gas station managers measure water content and monitor fuel content in gas station tanks automatically and realtime so that fuel quality is maintained, information can be monitored through web-based systems and mobile applications with Internet of Things technology. The IoT system design consists of an Arduino Uno R4 microcontroller, an ultrasonic sensor HC-SR04 to measure the contents of the tank level, a conductivity sensor to measure the moisture content contained in the fuel while a temperature sensor to measure the temperature inside the tank and a selenoid valve to remove the water in the tank. The accuracy test results of the ultrasonic sensor used are good enough to measure the contents of the tank with an average error of 1.3%, while the conductivity sensor measurement has an average error of 0.292% with the validation process using the centrifuge method, the temperature sensor has an accuracy of 1.6%. The selenoid valve works well which is activated through a web-based monitoring app and a mobile app.